Chronic persistent parvovirus B19 bone marrow infection resulting in transfusion-dependent pure red cell aplasia in multiple myeloma after allogeneic haematopoietic stem cell transplantation and severe graft versus host disease. Issue 2 (7th February 2017) - Karrasch, Matthias; Schmidt, Volker; Hammer, Andreas; Hochhaus, Andreas; Rosée, Paul La; Petersen, Iver; Sauerbrei, Andreas; Baier, Michael; Sayer, Herbert G.; Hermann, Beate
Abstract : Introduction : We report a chronic persistent Parvovirus B19 (PVB19) infection despite long-term immunoglobulin substitution intravenous immunoglobulin (IVIG) and tapering of immune-suppressive therapy in a 41-year-old patient after allogeneic haematopoietic stem cell transplantation (alloHSCT) and long-term immune-suppressive therapy due to a steroid-refractory graft versus host disease (GvHD). Clinical course : More than 18 month after alloHSCT the patient acquired a de novo transfusion-dependent pure red cell aplasia (PRCA) due to a PVB19 infection. Despite prompt tapering of GvHD-directed therapy and application of various IVIG regimens, transfusion-dependent anaemia (fourerythrocyte concentrates a month) persisted, and a high PVB19 replication is still evident for more than 3.5 years. Virological analysis at different time points showed a very high PVB19 load in the blood (range: 6.79E9–1.56E11), as well as highly elevated PVB19-IgG (range: 1.95–3.34) and -IgM (range: 1.97–9.74) levels in serology testing. Other virological parameters were not significantly elevated. After 30 months, a bone marrow (BM) examination still revealed a highly dysplastic erythropoiesis without any cellular maturation, and a high-grade expression of PVB19 within the dysplastic erythropoietic progenitor cells, consistent with a PRCA due to a PVB19 infection of the BM. We suggest that PRCA was most probably caused by a primary PVB19 infection of unknown source following alloHSCT with a PVB19-negative donor. Conclusion : PRCA due a PVB19 infection of the BM may persist over a long-time, despite prolonged administration of various IVIG regimen and tapering of GvHD-directed therapy. The case emphasizes the importance of PVB19 monitoring in heavily pre-treated haematological patients. Currently, PVB19-directed treatment options are extremely limited and optimized therapeutic strategies are urgently needed.